A Study of Slope Stability under Seismic Loads at Navaminda Kasatriyadhiraj Royal Air Force Academy, Mittraphap Subdistrict, Muak Lek District, Saraburi Province - Sangthongtong, Arissaman; Nitiwong, Pongrit (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This research studied the stability of soil slopes under seismic loads at Navaminda Kasatriyadhiraj Royal Thai Air Force Academy, Mittraphap Subdistrict, Muak Lek District, Saraburi Province. The objective of this research is to examine the Factor of Safety (F.S.) for slope stability and the displacement behavior of soil layers in both horizontal and vertical directions at a horizontal distance of 2 meters from the slope. This study investigated the stability at three slope inclination levels: 1:1, 1:2, and 1:3 of soil type C (0.0465 g) and type D (0.0656 g) which supported the weight of a 6-story residential building. These slopes were subjected to the impact of seismic loads in terms of the spectral response acceleration, which was calculated by the equivalent static force method according to the Department of Public Works and Town & Country Planning standards (DPT 1301/1302-61). The soil parameters from the Boring Log reports were utilized in the analysis using the two-dimensional finite element method. The soil profile was modeled employing the Mohr-Coulomb approach, comprising clay layers (Undrained model), sand layers (Drained model), and hard soil layers, which were assumed to be tightly bonded and capable of transmitting energy to each other. The results indicated that soil type C has a higher F.S. than soil type D, with the F.S. fluctuating according to the slope inclination ratios of 1:1, 1:2, and 1:3, respectively. In terms of displacement in both directions, soil type D exhibited greater movement than soil type C, with displacement varying according to the slope inclination ratios of 1:3, 1:2, and 1:1, respectively.